SOSIALISASI DAN PENDAMPINGAN PEMBELAJARAN PAUD BERBASIS HYBRID BAGI GURU LEMBAGA PENDIDIKAN ANAK HEBAT INDONESIA (AHE) DI KEC. TUMPANG, KAB. MALANG - Suhartatik Suhartatik; Titik Purwati; Wilyati Agustina Bangun (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P2M) IKIP Budi Utomo Malang, 2022)
The evolution of education for early childhood (PAUD) is very crucial in digital period, in order to adapt currently situation and conditions. The teachers have to be able to create and develop various media that fitted with the child’s age and characteristics. The objective of hybrid- based learning assistance for early childhood education (PAUD) aims to offer the comprehension for the teacher how to absorb and develop teaching method and media for early childhood by using various resources. This activity covers some agendas i.e initial activities, implementation and evaluation. The target of the activities are expected that the teachers are able to catch on hybrid-based learning, moreover the teacher are able to develop internet-based media for teaching PAUD, and they can utilize innovative teaching aids. The last, the activity will contribute the output of scientific publication.